FORMS AND METHODS OF INTERACTION OF SCHOOL AND LOCAL SELF-GOVERNMENT IN THE PROCESS OF SCHOOLCHILDREN’S CIVIC EDUCATION - Zhadko, Olena (Educological discourse, 2020)
The article is dedicated to the revelation of forms and methods of interaction of school and local self-government when implementing schoolchildren’s civic education. The main forms and methods of this interaction are: support of the activities of socially active schools aimed at providing the academic, health maintaining, entertaining and social services and providing training programs for people’s professional activity, ensuring the implementation of projects and programs in civic education (in particular, Swiss-Ukrainian project "Development of Citizenship Competences in Ukraine", Ukrainian project "Zero Waste School", youth project "Deputy quest" etc.), support of the activities of regional youth school organizations ("Youth Parliamentary Club", in particular), conducting actions on schoolchildren’s civic education (for instance, "For a Clean Environment", "Citizen" etc.), organization and facilitation of the work of museums, holding children’s festivals, regional contests dedicated to different educational and cultural problems, schoolchildren’s competitions in subjects, competitions (tourism and local history, sporting, intellectual etc.), tournaments, festivals, games, meetings, excursions and exhibitions dedicated to important dates and events in the life of the country, its history, outstanding people and nature, seminar-practicum in youth civic education, production and distribution of information materials about native land. Due to above-mentioned forms and methods of interaction of school and local self-government, schoolchildren can take active part in community life, introduce non-standard, innovative approaches to solving the problems of local communities and modern managerial and information technologies in local government.